Studi Faktor Penyebab Keterlambatan Penyelesaian Pekerjaan Konstruksi Gedung di Universitas Islam Lamongan - Damara, Bobby; Mudjanarko, Sri Wiwoho; Moetriono, Hary (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2024)
Schedule delays or increased construction calendar periods are problems that are often encountered in construction project work and can be caused by several factors including managerial factors, implementation methods, work environment and so on, during the construction of buildings at the Islamic University of Lamongan in 2015-2018 there were delays in several buildings or infrastructure built by the university in this study the researchers made efforts to obtain or find out the main supporting factors that influence delays by means of a survey distributing questionnaires to parties with a direct interest in construction project work. The ranking method is used to determine the ranking of respondents which can later be used as a reference as to why the construction of campus buildings is delayed, Data analysis in this study uses multiple linear regression analysis stepwise method based on the results of the analysis of variable X7 (implementation method) is the most dominant factor in time delays obtained coefficient value 0, 924 or 92.4% with a multiple linear regression equation Y = 0.962 + 0.924 (X7) and the results of the β coefficient value, obtained the following ranking The implementation method factor (X7) with a β coefficient value of 0.924, financial factors (X5) with a β coefficient value of 0.171, managerial factors (X8) with a β coefficient value of 0.040. Design factor (X2) with a β coefficient value of 0.031, Labor factor (X1) with a β coefficient value of -0.017, Work environment factor (X3) with a β coefficient value of -0.063. Material / material factor (X4) with a β coefficient value of -0.064, Equipment factor (X6) with a β coefficient value of -0.136, Based on the results of the analysis obtained for construction service providers who carry out development work, must apply good and efficient implementation methods in all stages of work.